A process-oriented approach to medication reconciliation at admission in a surgery department. Issue 2 (12th March 2012) - Curatolo, N.; Assoukpa, J.; Desnoyer, A.; Haddad, R.; Courtin, C.; Dagher, I.; Rieutord, A.
Abstract : Background: The 2007 WHO guidelines underscore the importance of using medicines reconciliation (MR) in hospitals in order to assure the correct medicines at transitions in care. Purpose: To develop a process-oriented approach in order to implement a MR process in an abdominal surgery ward. Materials and methods: This study was divided into three parts of 1 month each. First, The authors compared the medicines history (MH) taken by the pharmacist with the physician's computerised prescription at admission. Unintended medication errors (UMD) were identified with the physician in order to obtain the mean number of UMD per patient. In the second study, the MH taken by the pharmacist was copied onto an MH form (MHF) that was used by the practitioner to help prescribe treatment at admission. Before beginning the third part, the MR process workflow was optimised by a multi-disciplinary working team. In the second and third part the average days to complete MHF and the mean number of UMD per patient were measured in order to assess the efficiency of our MR process. Results: 44 (average age 53, 3.4 treatments/patient), 50 (average age 50.5, 2.9 treatments/patient) and 55 (average age 48.3, 2.3 treatments/patient) patients were included in parts 1, 2 and 3 respectively. UMDs per patient decreased from 0.41 in part 1 to 0.24 in part 2 and 0.25 in part 3. Workflow optimisation before the third part led to the pharmacist performing MHF for scheduled patients before their admission. Average days to complete the MHF decreased from 1.1 to 0.82 between parts 2 and 3. Conclusions: Our approach, which was to introduce small improvements, communicate actively with the clinical unit and improve the workflow enabled us to successfully introduce MR into the abdominal surgery unit. The MR process now relies on a structured organisation and no longer on individuals.